Testing the morale theory of nominal wage rigidity - Daiji Kawaguchi; Fumio Ohtake (Osaka University, Institute of Social and Economic Research (ISER), 2004)
This paper attempts to test the morale theory of nominal wage rigidity by identifying the causal effect of pay cuts on workers' income satisfaction and work morale. This paper uses the current deflationary recession in Japan to estimate this causal effect. Our original survey of Japanese firms and their employees conducted in 2000 revealed that about 17 percent of our sample experienced a nominal, annual income decline. These wage cuts severely decreased income satisfaction and work morale. We consider several channels through which pay cuts deteriorate workers' pay satisfaction and work morale. We found that an income freeze demoralizes workers by reducing workers' trust in their firms, but an income decline decreases work morale even after controlling for this reduction of trust. Allowing for the firm fixed effects does not alter the robust relationship between the income cut and demoralization. Overall, our results consistently indicate the adverse effect of income cuts on workers' pay satisfaction and morale. This evidence, obtained from a deflationary economy, supports Bewley (1999)'s morale theory of nominal wage rigidity.
Keywords: 330; Lohnrigidität; Deflation; Arbeitsethik; Arbeitsproduktivität; Japan